Climate Change & Just Energy Transition: What the North Can Learn from the South? - Munir Khasru, Syed; Ambrizzi, Tércio (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
The G20, a group of the world’s largest economies, has the unique potential to catalyze change in climate actions and a just energy transition. It is essential to consider the importance of these topics for the G20 and what to look forward to in Brazil’s Presidency. The upcoming Summit presents a pivotal moment for G20 nations to unite in their resolve to combat climate change and steer the world toward a future defined by environmental sustainability and energy justice.